Long-Term Outcomes in Patients With Non-Ampullary Duodenal Neuroendocrine Tumors - Da-Bin Jeong; Sang-Gyun Kim; Soo-Jeong Cho (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Objectives Although non-ampullary duodenal neuroendocrine tumors (NADNETs) are rare neoplasms, their incidence has been increasing. In this study, we aimed to analyze the long-term outcomes of patients with NADNETs who underwent endoscopic resection (ER) or surgery. Methods This retrospective study included 55 adults (aged 26–78 years) diagnosed with NADNETs between 2009 and 2022 at Seoul National University Hospital. We categorized the patients into 3 groups: 21 underwent ER, 28 underwent surgical resection, and 6 had no detectable residual tumors after the initial biopsy during the follow-up period. Continuous data were examined using the Mann–Whitney U or Kruskal–Wallis tests, and categorical variables were analyzed using the χ2 or Fisher’s exact tests. Results A total of 21 patients, with a mean tumor size of 9.2±5.3 mm, underwent successful ER. After ER, three patients experienced perforation (14% [3/21]); two underwent primary repair surgery, and one recovered with conservative treatment. The mean tumor size of 28 patients who underwent surgical resection was 13.9±6.7 mm. There were no cases of postoperative bleeding or perforation; however, four patients experienced ileus and required prolonged hospital stays. The median follow-up periods for patients who underwent ER, surgical resection, and removal after the initial biopsy were 42, 48, and 42.5 months, respectively. During the follow-up period, no recurrence was observed in any group. Conclusions Recurrence-free survival in patients undergoing ER for NADNETs, with an endoscopically measured size of approximately 10 mm, was comparable to that of patients undergoing surgical resection. However, ER carried a relatively high risk of perforation due to the challenging anatomical access and thin duodenal wall.